2019
DOI: 10.2174/1570180816666181212153011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Thiohydantoins Obtained from L-Amino Acids

Abstract: Background: Thiohydantoins are an important class of heterocyclic compounds in drug discovery since they are related to a wide range of biological properties including antimicrobial activity. Objective: The objective of this study was to synthesize a series of thiohydantoins derived from Laminoacids and to evaluated their inhibitory effect on the growth of Gram-negative and Grampositive bacteria. Methods: All title compounds were synthetized by reaction of L-amino acids with thiourea or ammonium thiocyana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Thiohydantoins ( 1 a – l ) were synthesized as previously described by de Carvalho et al., 2020 [20] . The in vitro antioxidant activity of thiohydantoins ( 1 a – l ) were determined by DPPH scavenging assays (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thiohydantoins ( 1 a – l ) were synthesized as previously described by de Carvalho et al., 2020 [20] . The in vitro antioxidant activity of thiohydantoins ( 1 a – l ) were determined by DPPH scavenging assays (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Other 2-thiohydantoin and rhodanine derivatives investigated by Tejchman et al [ 2 ] demonstrated no activity against Gram-negative bacteria, but some of them were active against Gram-positive ones. Thiohydantoins reported by Camargo de Carvalho et al [ 3 ] were more effective against Gram-positive bacteria, as well. The possible antibacterial mechanism of the hybrids of 2-thiohydantoin and rhodanine derivates reported by Tejchman et al [ 2 ] suggests “their interaction with molecular targets located on the surface of the cell membrane”.…”
Section: Resultsmentioning
confidence: 89%
“…Among already applied drugs, quinolones and thiohydantoin derivatives are used as chemotherapeutics and antibiotics. Compounds containing 2-thiohydantoin core reveal antibacterial [ 1 , 2 , 3 ], antifungal [ 4 ], antitumor [ 5 ], antiparasitic [ 6 ], and antiviral activity [ 7 ]. Compounds with 2-quinolone core are also known for their broad range of biological effects [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results illustrated a significant difference ( P < 0.05s) between the inhibition rate of treated biofilms and untreated biofilms. Consequently, the potential of exhibiting antibiofilm activity against biofilms of S. aureus is more by these compounds compared to the previous reports (it inhibited 40% S. epidermidis ATCC 12228 biofilm) [ 82 ]. So far, only a few studies have been found about inhibited biofilms by hydantoin compounds.…”
Section: Resultsmentioning
confidence: 91%
“…Generally, the compounds showed potentiating properties at concentrations from 31 to 125 µg/mL. us, these compounds have more potential than previously reported anti-S.aureus activity MIC values [80][81][82]; in addition to the tested bacteria, there are other virulent strains. Hydantoin derivatives are small molecules that have moderate antimicrobial activity which may be essential for reducing antibiotic resistance in the long run, besides being potent and having rapid antimicrobial activity against pathogenic bacterial strains [83].…”
Section: Minimal Inhibitory Concentrations (Mics) Of the New Hydantoi...mentioning
confidence: 93%